Faktor-Faktor yang Berhubungan dengan Tingginya Angka Open Defecation (OD) di Kabupaten Jember (Studi di Desa Sumber Kalong Kecamatan Kalisat) Factors Assosiated with High Number of Open Defecation (OD) in District Jember (Studies in Sumber Kalong Village - Wahyu Afiatul Qudsiyah; Rahayu Sri Pujiati; Prehatin Trirahayu Ningrum (Pustaka Kesehatan, 2015)
Community-Led Total Sanitation (CLTS) is an approach to hygiene and sanitationbehavior change through community empowerment by triggering method. DistrictJember in 2013, recording 61,54% of households that already have access tolatrines. The Strategic Plan District Jember for family latrines in 2014, that is 86%,target of MDGs in 2014 that is 75%. Sumber Kalong village is the high number OD inDistrict Jember that is 92,04%. The purpose of this study was to determine factorsassociated with high number Open Defecation (OD) in District Jember (study inSumber Kalong village Subdistrict Kalisat). The study is an observational study withcross sectional approach. Total Sample of responden was 35 housewife/heads offamilies with proportional random sampling technique. Data analyzed using Chisquaretest (α=0,05).The results showed associated between knowledge, attitude,latrine ownership, distance from the house to defecation except latrinest, familysupport, community support with high number of OD. However, there was noassosiated age, gender, education, employment, income, type latrine, latrineconditions, supply of clean water and support health workers with high number of OD.Keywords : Community-based total sanitation, Open defecation